THE PLACE OF SIGN LANGUAGE IN THE INCLUSIVE EDUCATION OF DEAF LEARNERS IN ZIMBABWE AMID CRPD (MIS)INTERPRETATION (African Disability Rights Yearbook, 2021)
This paper sets to explore how Zimbabwean law and policy relate to the CRPD in informing educational practice for learners who are deaf. The paper is an analytical discussion of the educational policy and practice issues related to the recent recognition of Zimbabwean Sign Language (ZSL) in a multicultural context where mother-tongue-based teaching is a right for meeting the inclusive education needs of all learners, including those who are deaf. It argues that one-size-fits-all, deficit interpretations of Zimbabwean inclusive education policies and law are in violation of the ‘sensory exception’ enshrined in the Salamanca Statement (UNESCO, 1994). These interpretations occur in the midst of major misinterpretations of the CRPD evident in General Comment 4. Misinterpretations of the CRPD affirm instances of local policy contradictions, inconsistencies and co-articulation as some policies are imbued with perceptions of deafness as a disability at the same time also having aspects that recognise deaf people as a linguistic minority. The deficit interpretations and inconsistencies in local policies occur despite constitutional provisions that recognise deaf learners’ right to a preferred sign language. Based on this case example of deaf learners, a general re-interpretation of the CRPD and a re-conceptualisation of inclusive education are recommended.
Keywords: CRPD; Zimbabwean law and policy; educational practice; deaf learners; Zimbabwean Sign Language; inclusive education policies